Biocementation of sand in geotechnical engineering - Maryam, Naeimi (2014)
In geotechnical engineering, conventional soil improvement techniques - including both mechanical and chemical stabilization methods - have potential drawbacks such as high cost, high energy consumption and sometimes negative environmental influences. However, the rapid development of biotechnology has provided opportunities for innovation in soil improvement methods. In recent years, a promising approach, the so-called microbial geotechnology, has been attempted. This study contributes to the development of biocement and its application to soil improvement. Using the microbially induced carbonate precipitation (MICP) process, calcium carbonate and other types of minerals can be generated and used to increase the shear strength and reduce the permeability of soil. The primary objective of this research is to study the mechanims for the optimization of the MICP process to increase the efficiency of calcite precipitation. For the first time, this study has showed that the urease activity in samples with bacterial cells was 70 + 3% more effective than that with a supernatant or intact cultural liquid. This can be explained by the presence of urease inactivating protease in the supernatant. In addition, an increase in the efficiency of cell aggregation in sand by 86% has been achieved after pretreating the sand with an addition of Ca2+ to the bacterial cells. This study also shows that cell aggregration on the surface of sand leads to a signicant increase in crystallization of calcite.